2021
DOI: 10.1109/access.2021.3077037
|View full text |Cite
|
Sign up to set email alerts
|

RobUSt–An Autonomous Robotic Ultrasound System for Medical Imaging

Abstract: Medical ultrasound (US) systems are widely used for the diagnosis of internal tissues. However, there are challenges associated with acquiring and interpreting US images, such as incorrect US probe placement and limited available spatial information. In this study, we expand the capabilities of medical US imaging using a robotic framework with a high level of autonomy. A 3D camera is used to capture the surface of an anthropomorphic phantom as a point cloud, which is then used for path planning and navigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…These end-effector poses are generated based on the surface geometry captured using the 3D camera and the positions of the vessel centroids derived from intraoperative US scan by using the vessel segmentation algorithm described in section II.A. Surface scanning and the impedance control used for realizing the robot motion are both described in our prior work [35]. Path planning algorithm developed for this application is designed to calculate a surface path for acquiring US images containing consecutive centroids in sagittal crosssection of the vessel.…”
Section: B Us Probe Visual Servoing On a Body Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…These end-effector poses are generated based on the surface geometry captured using the 3D camera and the positions of the vessel centroids derived from intraoperative US scan by using the vessel segmentation algorithm described in section II.A. Surface scanning and the impedance control used for realizing the robot motion are both described in our prior work [35]. Path planning algorithm developed for this application is designed to calculate a surface path for acquiring US images containing consecutive centroids in sagittal crosssection of the vessel.…”
Section: B Us Probe Visual Servoing On a Body Surfacementioning
confidence: 99%
“…Based on this notion, a study by Zettinig et al [34] showed that US visual servoing can be used for neurosurgical navigation and needle guidance. Furthermore, in our previous studies, we have demonstrated both optical visual servoing [21] and impedance control [35] used for body motion compensation while performing robotic US scanning along the planned surface path.…”
Section: Introductionmentioning
confidence: 99%
“…According to the average distance from point pi to the neighboring points, the point cloud noise is removed, as shown in Equation (12). 12), the points will be reserved, otherwise, the points will be removed.…”
Section: Path Extraction a Point Cloud Denoisingmentioning
confidence: 99%
“…Robots can assist doctors in completing breast ultrasound examinations, thus reducing the work intensity of doctors. Robots can accurately complete repetitive scanning operations to improve examination efficiency, standardize operation processes and reduce labor costs [10]- [12]. The robot for breast ultrasound examination requires high precision and efficiency to meet the scanning requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing autonomous systems are still at level 2 [27][28][29][30], which rely on experts to design the acquisition procedure. Although some systems can reach level 3 (i.e., [31][32][33][34]), their clinical feasibility must be investigated further and compared with robotic assistant systems. To this end, fully autonomous robotic diagnosis is still challenging, as it calls for more perception, planning and control on the part of the robot.…”
Section: Introductionmentioning
confidence: 99%